Aspectos paleoambientais do Quaternário Superior na região de Campo Mourão, Paraná - Luz, Leandro Domingos (2014)
Campo Mourão region (24º 06' S - 52º 23' W) composes an enclave of Savanna vegetation in the Araucaria Forest and Seasonal Semideciduous Forest transition. The present research proposes to characterize the peaty sediments of the region and use different data proxies (phytolith analysis and stable isotopes of C and N), associated to absolute dating (14C), that could infer about the paleoenvironmental conditions in the studied area. Furthermore, we analyzed two cores with peaty sediments of Água dos Papagaios and Ranchinho river floodplain. The data obtained was correlated with the isotopes values of the Soil Organic Matter (SOM) established in the Estação Ecológica do Cerrado (EEC), where it was opened a trench with 3 (three) meters deep. The samples of peaty sediments were processed with hydrochloric acid (10%) and potassium hydroxide (10%). We applied the conventional method used in palynology studies, that consist in acid attach and suspension with dense liquid with positive result for phytolith analysis. We counted 200 phytoliths for sequence that were classified using the International Code for Phytoliths Nomenclature 1.0 and were established the phytoliths indexes disposed in the international lecture. We stated the 14C dating and isotopes values (δ¹³C and δ15N) of the samples. We elaborated topography profiles in the area that help us to observe the occurrence of terraces. Concerning the peaty bogs characterization we obtained: i) low burn power (volatile and solid) of the peaty, indicating the unfeasible use for energetic proposes; ii) characterization of von Post scale showing a Sapric condition on base, Hemic in the middle and Fibrous on the top. The phytoliths data and the isotopes values allowed the following paleoenvironmental interpretation: i) From 48.800±270 years BP. to ~41.146 cal years BP. (dry phase), probably predominance of grass (Savanna) and occurrence in this period of agradation processes in the Ranchinho river foodplain, building the base of the first terrace; ii) ~41.146 cal years BP. (less drier phase than the last) with presence of morphotypes (Globular) characteristic of botanic families that represent more humid (e.g. Arecaceae, Bromeliacae and others) in this phase has increase of the vegetation density, although with the grass vegetation yet - building the terrace in the Ranchinho river; iii) dry phase in the Pleistocene/Holocene transition; iv) probable base formation of the second terrace in the Ranchinho river and Água dos Papagaios during the Middle Holocene (~7.280 cal years BP.); v) C4 plants condition previously to 5.280 cal years BP. on EEC with isotope value impoverishment just on the top suggesting that the advance of plant formations (Araucaria Forest and Seasonal Semideciduous Forest) is recent in the studied area.